Pengembangan Perangkat Pembelajaran Matematika Berbasis Kontekstual pada Pokok Bahasan Perbandingan - Ismail, Risma; Abrar, Andi Ika Prasasti; Nur, Fitriani; Suharti, Suharti; Halimah, Andi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
The learning process cannot be separated from the use of learning tools, the entire learning process has been planned in these learning tools. This study aims to produce a contextual-based mathematics learning tool on the subject of comparison of class VII SMPN 27 Makassar which is valid, practical and effective. The type of research used is research and development (R&D) with reference to the 4-D Thiagarajan model, namely: (1) the define stage, (2) the design stage, (3) the develop stage, and (4) the disseminate stage. The instruments used were validation sheets, student response questionnaires, observation sheets for device implementation, and learning outcomes tests. Based on the results of the validation of the experts, the products developed and the instruments used for each aspect were in the